2023
DOI: 10.1002/adfm.202303423
|View full text |Cite
|
Sign up to set email alerts
|

Domain Distribution Management of Quasi‐2D Perovskites toward High‐Performance Blue Light‐Emitting Diodes

Abstract: Quasi‐2D perovskites, as one of the promising materials applied in perovskite light‐emitting diodes (PeLEDs), have attracted great attention for their superior semiconductor properties. The inherent multiquantum well structure can induce a strong confinement effect, which is especially suitable for blue emission. However, compared to their green counterparts, blue emitters constructed from quasi‐2D perovskites are more sensitive to n domain distribution (where n represents the number of PbX6 inorganic layers).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 145 publications
1
17
0
Order By: Relevance
“…Additionally, the full-width at half-maximum (FWHM) of the PL spectra decreases from 27 to 18 nm with the increasing ratio of L-PMeCl from 0% to 100%. This suggests that the L-PMeCl treatment controls the crystallization process and reduces the coexistence of multiple small-n phase perovskites, [39] which is in accord with the absorption analyses (Figure 1b).…”
Section: Effect Of Pmecl On Quasi-2d Perovskite Filmssupporting
confidence: 81%
See 1 more Smart Citation
“…Additionally, the full-width at half-maximum (FWHM) of the PL spectra decreases from 27 to 18 nm with the increasing ratio of L-PMeCl from 0% to 100%. This suggests that the L-PMeCl treatment controls the crystallization process and reduces the coexistence of multiple small-n phase perovskites, [39] which is in accord with the absorption analyses (Figure 1b).…”
Section: Effect Of Pmecl On Quasi-2d Perovskite Filmssupporting
confidence: 81%
“…L-PMeCl-based films may avoid the adverse effects of poor charge transport and non-radiative recombination caused by small-n phases. [38,39] Upon increasing the concentration of PMeCl from 0% to 100%, the PL peaks of perovskite films gradually blueshift from 498 to 484 nm (Figure 1c), while the bandgap changes from 2.42 to 2.49 eV (Figure S2, Supporting Information). These are probably attributed to the incorporation of Cl − from L-PMeCl into the perovskite lattice.…”
Section: Effect Of Pmecl On Quasi-2d Perovskite Filmsmentioning
confidence: 99%
“…2 It is widely accepted that the inorganic MX 6 4− octahedral cube sheets possess higher dielectric constants, while large organic spacer cations have relatively lower dielectric constants. 3 Since MX 6 4− octahedral cube sheets can be blocked by L large organic cations to form small-n domains with large exciton binding energy (>100 meV), the quasi-2D perovskite layer has more obvious exciton behavior compared with the three-dimensional counterpart. 4,5 Efficient domain distribution control is especially important for a blue quasi-2D perovskite layer.…”
Section: Introductionmentioning
confidence: 99%
“…In the L 2 A n –1 M n X 3 n +1 molecular formula, L is usually a large organic spacer cation, A is a monovalent cation, M is a divalent metal cation, X is one or a mixed halide anion, and n is the number of MX 6 4– octahedral cube sheets sandwiched between the L large organic spacer cation . It is widely accepted that the inorganic MX 6 4– octahedral cube sheets possess higher dielectric constants, while large organic spacer cations have relatively lower dielectric constants . Since MX 6 4– octahedral cube sheets can be blocked by L large organic cations to form small- n domains with large exciton binding energy (>100 meV), the quasi-2D perovskite layer has more obvious exciton behavior compared with the three-dimensional counterpart. , Efficient domain distribution control is especially important for a blue quasi-2D perovskite layer .…”
Section: Introductionmentioning
confidence: 99%
“…Further comparison of these calculated band positions to those of 3D CsPbBr 3 (Figure c) make it clear that, if the 3D phase exists in a mixed n phase sample, carrier funneling would heavily favor radiative recombination at 525 nm (the PL emission wavelength for 3D CsPbBr 3 ). Indeed, many reports have shown that the suppression of the 3D phase and control of the 2D phase distribution in thin films are critical for LEDs and other optoelectronic devices. , Conversely, when making claims about LED or even lasing from related 2D RP perovskites, caution must be taken to rule out light emission from 3D perovskite rigorously.…”
mentioning
confidence: 99%